2015
DOI: 10.1080/15575330.2015.1062035
|View full text |Cite
|
Sign up to set email alerts
|

The influences of community attachment, sense of community, and educational aspirations upon the migration intentions of rural youth in Texas

Abstract: Data drawn from the Rural Youth Community Survey were used to examine the associations of community attachment, sense of community, and educational aspirations of rural youth in Texas with their migration intentions. Multivariate logistic regression revealed that the three measures are independently and significantly associated with students' intentions to migrate. Based upon these findings, several recommendations for community leaders hoping to retain youth in rural areas and/or encourage young people to ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 18 publications
(20 reference statements)
6
35
0
6
Order By: Relevance
“…Stanovnici s višim doživljajem zajednice bit će zadovoljniji zajednicom (Lardier, 2018), više će se identificirati s njom i imati više povjerenja u lokalnu vlast kao i višu razinu interpersonalnog povjerenja (Prezza i sur., 2009). Mladi s višim doživljajem zajednice, posebice u dimenziji članstva i višom pripadnosti, imat će izraženije namjere ostanka u zajednici (Theodori i Theodori, 2015). Autori Theodori i Theodori (2015) ističu da će namjere ostanka iskazati mladi sa srednjim obrazovnim aspiracijama te se potvrđuje da je upravo ta skupina mladih ona koja može predstavljati polugu demografskog osnaživanja u slabije razvijenim zajednicama.…”
Section: Doživljaj Zajedniceunclassified
See 1 more Smart Citation
“…Stanovnici s višim doživljajem zajednice bit će zadovoljniji zajednicom (Lardier, 2018), više će se identificirati s njom i imati više povjerenja u lokalnu vlast kao i višu razinu interpersonalnog povjerenja (Prezza i sur., 2009). Mladi s višim doživljajem zajednice, posebice u dimenziji članstva i višom pripadnosti, imat će izraženije namjere ostanka u zajednici (Theodori i Theodori, 2015). Autori Theodori i Theodori (2015) ističu da će namjere ostanka iskazati mladi sa srednjim obrazovnim aspiracijama te se potvrđuje da je upravo ta skupina mladih ona koja može predstavljati polugu demografskog osnaživanja u slabije razvijenim zajednicama.…”
Section: Doživljaj Zajedniceunclassified
“…Mladi s višim doživljajem zajednice, posebice u dimenziji članstva i višom pripadnosti, imat će izraženije namjere ostanka u zajednici (Theodori i Theodori, 2015). Autori Theodori i Theodori (2015) ističu da će namjere ostanka iskazati mladi sa srednjim obrazovnim aspiracijama te se potvrđuje da je upravo ta skupina mladih ona koja može predstavljati polugu demografskog osnaživanja u slabije razvijenim zajednicama. Doživljaj zajednice povezan je s jačim socijalnim kapitalom na individualnoj i na kolektivnoj razini (Perkins i Long, 2011).…”
Section: Doživljaj Zajedniceunclassified
“…Instead, policymakers are urged to "replace the principle of retaining youth" with principles that increase the range of "viable alternatives" for young people by focusing equally on the development of "supports to leave" and "supports to stay" (Shucksmith, 2004:55;cf. Jones, 1999;Jones, 2004;Kloep et al, 2003;Nugin, 2014:62;Theodori & Theodori, 2015). In practice, this means improving young peoples' social and economic integration and civic involvement within rural communities from very early on, and focusing retention and attraction efforts more closely on those people who already want to stay in, come, or return to rural areas (Jentsch, 2006:236).…”
Section: Recommendationsmentioning
confidence: 99%
“…It has been repeatedly revealed that the factors restraining migration activity are close ties with people in the residence place, the presence of family, friends, high val-ue of the existing relations [25][26][27][28]. Some scientific studies point out a desire for ca-reer growth [29][30][31], improving their education, entertainment opportunities [32] as motives for migration.…”
Section: Introductionmentioning
confidence: 99%